If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + x = -5x + 59 Reorder the terms: 5 + x = 59 + -5x Solving 5 + x = 59 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 5 + x + 5x = 59 + -5x + 5x Combine like terms: x + 5x = 6x 5 + 6x = 59 + -5x + 5x Combine like terms: -5x + 5x = 0 5 + 6x = 59 + 0 5 + 6x = 59 Add '-5' to each side of the equation. 5 + -5 + 6x = 59 + -5 Combine like terms: 5 + -5 = 0 0 + 6x = 59 + -5 6x = 59 + -5 Combine like terms: 59 + -5 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 3n^2+15n-150=0 | | 1+x+2x^3+3x^5=0 | | X=-5y+46 | | -2t+3b+4t= | | Log(x)=3.6 | | 267=5x+4(6x+16) | | 2667=5x+4(6x+16) | | x+y-z=n | | 45/12=5y | | 12X-12=18*14X | | 6x^2-2x-5= | | -34=3x-2(4x+32) | | 2X+2-3.2X=8 | | 3x+7x-6=0 | | y=-0.05x^2+100x-12000 | | 4=-4x^3 | | 2=1/4x^2 | | -1127=-7(-11x-26) | | 4x-30=x+50 | | F(-2)=0.5(2-(-2)) | | -2+j= | | 3/y-8=5 | | 4xsquared+2c-1=0 | | 8x(3-2x)(4-x)=0 | | 3x-5/5-2x | | 9x-1=12x-8 | | 1-10x=80 | | 0.01t^2-0.5t+18=0 | | x/-3.1=4.5 | | (3y)^1/3 | | 5x^2-7x+20=0 | | 12(1.5)+4= |